2013
DOI: 10.1007/978-1-4614-6130-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Taurine Exposure Programs Patterns of Autonomic Nerve Activity Responses to Tooth Pulp Stimulation in Adult Male Rats

Abstract: Perinatal taurine excess or deficit influences adult health and disease, especially relative to the autonomic nervous system. This study tests the hypothesis that perinatal taurine exposure influences adult autonomic nervous system control of arterial pressure in response to acute electrical tooth pulp stimulation. Female Sprague-Dawley rats were fed normal rat chow with 3% β-alanine (taurine depletion, TD), 3% taurine (taurine supplementation, TS) or water alone (control, C) from conception to weaning. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…b-alanine is a competitive inhibitor of taurine to the taurine transporter activity. 1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations.…”
Section: Discussionmentioning
confidence: 99%
“…b-alanine is a competitive inhibitor of taurine to the taurine transporter activity. 1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal taurine deficiency leads to impaired development of central nervous system (particularly the autonomic nervous system control areas) and to impaired learning and memory in adult life. Perinatal taurine imbalance alters patterns of renal sympathetic nerve activity (Khimsuksri et al 2012). Perinatal taurine imbalance also alters autonomic nervous system control of arterial pressure in adult rats.…”
Section: Perinatal Taurine Exposure Affects Adult Arterial Pressurmentioning
confidence: 99%
“…One of the existing approaches to study the role of taurine in tissues such as the retina is to induce its systemic depletion using pharmacological treatments [ 1 , 4 , 5 ] and then studying the alterations triggered in the target tissue, i.e., the retina. It is well established that the administration of β-alanine on the drinking water of rats at a concentration of 3% causes a decline in taurine plasma levels [ 4 , 6 , 39 , 40 , 41 , 42 ] and loss of photoreceptors and retinal ganglion cells [ 27 , 43 ]. Moreover, light exposure has been shown to worsen the harmful effects of taurine depletion [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%